2020
DOI: 10.1177/1945892420930938
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Approaches to the Medial Intraconal Space: Comparison of Transethmoidal and Prelacrimal Corridors

Abstract: Background Endoscopic transethmoidal and prelacrimal approaches can access the medial intraconal space (MIS). Objective This study aimed to compare advantages and drawbacks of these two approaches, and to explore their appropriate indications for management of lesions at various locations within the MIS. Methods Six injected cadaveric specimens were dissected using an endonasal approach performing a transethmoidal approach on one side and a prelacrimal approach on the contralateral side. The MIS was divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…28,29 Thus, as the clinical case presented in this study, the OPSL may serve as a reliable marker to prevent inadvertent damage to the orbital contents when addressing lesions in the PPF not beyond the lateral border of the OPSL. 30 Likewise, for surgeries in the medial orbit, staying above the lateral border of OPSL could potentially avoid damage to structures within the PPF.…”
Section: Inferior Bordermentioning
confidence: 99%
“…28,29 Thus, as the clinical case presented in this study, the OPSL may serve as a reliable marker to prevent inadvertent damage to the orbital contents when addressing lesions in the PPF not beyond the lateral border of the OPSL. 30 Likewise, for surgeries in the medial orbit, staying above the lateral border of OPSL could potentially avoid damage to structures within the PPF.…”
Section: Inferior Bordermentioning
confidence: 99%
“…Other studies that are impactful in the realm of endoscopic surgery, includes a cadaver study by Li et al 14 on surgical techniques to access the medial intraconal space (MIS) and a meta-analysis by Vinciguerra, et al 15 on two treatments options for Epiphora: external vs endoscopic approaches. In the first study, Li et al 14 compared the advantage and disadvantage of transethmoidal and prelacrimal approaches to access the medial intraconal space (MIS), and reported that while both approaches are capable to assess MIS, each approach has its own advantages for assessing different zones within the MIS. The 2nd study 15 attempted to examine different post-surgical medical therapies that may improve surgical outcomes of external dacryocystorhinostomy (EXT-DCR) and endoscopic endonasal dacryocystorhinostomy (END-DCR).…”
Section: Head Neck Cancer and Endoscopic Surgerymentioning
confidence: 99%
“…Other studies that are impactful in the realm of endoscopic surgery, includes a cadaver study by Li et al. 14 on surgical techniques to access the medial intraconal space (MIS) and a meta-analysis by Vinciguerra, et al. 15 on two treatments options for Epiphora: external vs endoscopic approaches.…”
Section: Head Neck Cancer and Endoscopic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…14 Its use has been widely expanded to remove tumors arising in the pterygopalatine fossa and infratemporal fossa, 15,16 as well as the management of lesions involving the orbital floor, inferior or medial intraconal space, lateral recess of sphenoid sinus, and middle cranial fossa. [17][18][19][20][21] Despite its limited instrument maneuverability, the advantages of a prelacrimal approach include sparing part of the lateral nasal wall, the nasolacrimal duct and posterior nasal septum. 14,15 Preservation of the aforementioned structures may be beneficial for maintenance of post-operative nasal function, which is particularly important when managing benign lesions.…”
Section: Introductionmentioning
confidence: 99%